Encephalocele within the Lateral Wall of the Sphenoid Sinus Presenting with Recurrent Meningitis and Cerebrospinal Fluid Rhinorrhea Repaired via Endoscopic Transnasal Transpterygoid Approach - Dipuo Masege; John Ouma (Indian Journal of Neurosurgery)
The sphenoid sinus is an uncommon site for an encephalocele. It usually presents with cerebrospinal fluid (CSF) leak through the nasal cavity. Sternberg's canal (SC), which is a weak spot on the skull base, is one of the causes of spontaneous CSF leak. It is due to incomplete fusion of the greater wing of the sphenoid bone with the basisphenoid. Repairing these defects is challenging as the traditional external approach carries a high morbidity and a high complication rate. We present the case of a 27-year-old nonobese female patient who was diagnosed with persistent SC defect, which was repaired via an endoscopic transnasal transpterygoid approach. She has not had any recurrence following 18 months of outpatient department visits.